Le partage culturel au service du développement à l’international de la « culture française » - Stela Raytcheva; Gilles Rouet (Communication)
The authors explore the construction of the interoperability of French “culture” and language at the international level through the network of Instituts français and Alliances françaises. They conclude that within a loose framework, the interoperability of French culture establishes itself through interconnections with a multitude of local cultures and cultural actors and by attracting, enlisting, and engaging the broadest possible audiences.